N2O hot moments were not driven by changes in nitrogen and carbon substrates or changes in N cycling functional genes. (11th November 2021) - Barrat, Harry A.; Charteris, Alice F.; Le Cocq, Kate; Abadie, Maider; Clark, Ian M.; Chadwick, David R.; Cardenas, Laura
Abstract: If a dry soil is wetted it can produce a large flush of nitrous oxide (N2 O), which can be 10 times above the background rate, this phenomenon is called a hot moment. However, there is uncertainty in the literature regarding the mechanisms that cause hot moments. Therefore, this study aimed to induce two different hot moments on soil cores to investigate changes in nitrogen (N) cycling functional genes, and correlate these changes with subsequent N2 O emissions, and transformations in soil chemistry. We induced a 'pre‐dry' treatment which wetted soils from 50% to 90% water‐filled pore space (WFPS) and 'pre‐wet' treatment which wetted soils from 70% to 90% WFPS to analyse changes in gas fluxes (N2 O, nitric oxide [NO] and carbon dioxide [CO2 ]), soil chemistry (pH, dissolved organic carbon [DOC], total oxidised nitrogen [TON], ammonium [NH4 + ]) and microbiology (bacterial 16S, fungal ITS and nitrogen cycling functional genes associated with denitrification). The soil produced emissions of N2 O that were significantly higher for the pre‐dry treatment compared with the pre‐wet treatment ( p = <0.001; 9 times that of the pre‐wet). The pre‐dry treatments did not prime the soil any more than the pre‐wet treatments for CO2 and NO emissions, and the results showed that the soils TON and DOC concentrations were significantly higher in the pre‐wet conditions despite its lower N2 O emissions. This suggests that the cause of the hot moment was not as dependant on the soil's substrate concentrations as previously thought. Moreover, the amount of denitrification genes in the pre‐dry soil was statistically similar to the pre‐wet ( nirK, norB, nifH, nosZI, nxrA ), apart from nirS which was marginally higher ( p = 0.03). Contrary to other experiments, this study provides evidence that changes in soil substrates and functional gene abundance are not the cause of N2 O hot moments. We therefore suggest that future studies should investigate changes in mRNA abundance related to N cycling genes. Highlights: Rewetting following drought caused a significant release of N2 O. The pre‐dry soil produced higher N2 O fluxes but contained less key substrates (TOC, NH4 + and DOC) than the pre‐wet soil. The pre‐dry and pre‐wet soil had a similar quantity of denitrification functional genes. Differences in soil chemistry and denitrification functional genes between the pre‐dry and pre‐wet soil cannot explain the differences in N2 O emissions.